The danger theory: 20 years later - Pradeu, Thomas; Cooper, Edwin L. (Frontiers in Immunology, 2012)
The self-nonself theory has dominated immunology since the 1950s. In the 1990s, Matzinger and her colleagues suggested a new, competing theory, called the “danger theory.” This theory has provoked mixed acclaim: enthusiasm and criticism. Here we assess the danger theory vis-à-vis recent experimental data on innate immunity, transplantation, cancers and tolerance to foreign entities, and try to elucidate more clearly whether danger is well defined.